What We Know Full Well - Jardine, David (Journal of the Canadian Association for Curriculum Studies, 2021)
This paper affirms that the complex and difficult insights of how teaching, learning and curriculum might shape themselves in light of current ecological alertness and concerns are well known and well documented.